2016
DOI: 10.3727/096368915x688209
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Improve Diabetic Neuropathy by Direct Modulation of Both Angiogenesis and Myelination in Peripheral Nerves

Abstract: Recent evidence has suggested that diabetic neuropathy (DN) is pathophysiologically related to both impaired angiogenesis and a deficiency of neurotrophic factors in the nerves. It is widely known that vascular and neural growths are intimately associated. Mesenchymal stem cells (MSCs) promote angiogenesis in ischemic diseases and have neuroprotective effects, particularly on Schwann cells. Accordingly, we investigated whether DN could be improved by local transplantation of MSCs by augmenting angiogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 57 publications
7
63
0
Order By: Relevance
“…Interestingly, inside the nerve parenchyma, ADSCs were detected in close proximity to intraneuronal vessels. Similar findings were demonstrated by Han et al after intramuscular injection of bone‐marrow derived MSCs (BM‐MSCs) in a diabetic neuropathy rat model . Stem cells were preferentially engrafted in the nerve parenchyma and partly localized in close proximity to vasa nervora of sciatic nerves.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, inside the nerve parenchyma, ADSCs were detected in close proximity to intraneuronal vessels. Similar findings were demonstrated by Han et al after intramuscular injection of bone‐marrow derived MSCs (BM‐MSCs) in a diabetic neuropathy rat model . Stem cells were preferentially engrafted in the nerve parenchyma and partly localized in close proximity to vasa nervora of sciatic nerves.…”
Section: Discussionsupporting
confidence: 82%
“…Several therapeutic strategies are being pursued to manipulate nerve plasticity and neurite outgrowth in diabetes, with the aim of encouraging axonal repair [161][162][163] . A study published in 2016 identified p75NTR as a novel therapeutic target in type 2 diabetes, on the basis of results using an adipocyte-specific conditional null mouse model shown to be resilient to high-fat-diet-induced obesity and insulin resistance 164 .…”
Section: Impact Of Schwannopathy On Neuronsmentioning
confidence: 99%
“…Bueno and colleagues also demonstrated improved insulin sensitivity in diabetic rats induced by a hyperlipidic diet and treated with MSCs intraperitoneally. The action of MSCs on insulin sensitivity in these studies is probably associated with their immunomodulatory role . No findings were analyzed in models with type 1 DM.…”
Section: Discussionmentioning
confidence: 90%